Carcass characteristics of adult sheep and goat breeds in the subhumid and semi-arid zones of Cameroon - Dawa, O.; Tawah, C.L.; Mawaina, T. (1996)
Data from slaughter (LWT) and warm carcass (HCWT) weights and dressing-out percentages (CYD%) of 209 Uda (Sahel) and 26 Djallonke sheep and 105 Djallonke goats were analysed by fitting a least-squares fixed-effects model. The model consisted of the effects of breed and sex on LWT and CYD% and the effects of breed, sex and LWT (as covariate) on HCWT for the sheep data. The effect of sex alone on LWT and CYD% was fitted for the goat data. As for the goat carcass data, HCWT was regressed on LWT for each sex subclass. Effect of breed significantly affected all carcass traits in the sheep. Effect of sex significantly affected all carcass traits in both species. Uda sheep were 19.2 kg heavier (P < 0.001) at slaughter, as expected, and produced 1.4kg heavier (P < 0.001) carcasses after adjusting to an equal LWT basis and 3.3 kg more meat per 100 kg LWT than Djallonke. Carcass weight was significantly linearly related (0.42±0.02 kg/kg) to live weight at slaughter in sheep. Entire (+6.8 kg) and castrated (+8.9 kg) males were significantly heavier than female sheep at slaughter. Castrates produced significantly heavier carcasses (+1.4 and + 1.3 kg, respectively) and significantly more meat per 100 kg LWT (+2.8 and +1.8 kg) than entire males and females. Castrated goats were 5.0 kg heavier (P < 0.001) at slaughter and produced 0.21 kg heavier carcasses (P